Volatilitas Harga Saham di Indonesia dan Malaysia - Kartika, Andi (Jurnal Ilmu Ekonomi ASET, 2010)
Disintermediatior phenomena in financial market show that many people tendto invest in capital market more than in banking. Thatâs happened, because the return onstock is profitable than banking interest rate. But, there is a big risk in capital market. Itâsnatural, financial market says that high risk high return, low risk low return. So, if we do notwant to loss, we must have ability to analyze stock performance, specially volatility of stock.This research useed ARCH/GARCH Model to estimate volatility. The research showed thatstock growth in 2007 â 2009 tended to decrease for all index (JSX and KLCI). JSX and KLCIjust had ARCH effect, so the index influenced volatility this time price index. The researchalso showed, that Î± value eâ 0,7 and sum of Î± and Î² almost one for all index (JSX and KLCI).That means, the volatility shock was persistent or the volatility was high and persistent.Â Keywords : ARCH, GARCH, volatility and persistent